ECHOCARDIOGRAPHY NOMOGRAMS IN BLACK SOUTH AFRICAN NEONATES - Prakaschandra, Rosaley; Hadebe, Nondumiso Memory; Beckerling, Bongiwe; Cilliers, Antoinette M.; Nsinjana, Hopewell N. (SA Heart Journal, 2024)
Quantitative estimation of cardiac chambers, valve annulus and great vessel dimensions in paediatric echocardiography is necessary in clinical management, but nomograms for these structures are limited, and there is paucity of data originating from sub-Saharan Africa. This study sought to establish echocardiography nomograms for cardiac chambers, valve annulus, great vessels and thymus dimensions in the Black South African neonatal population. Objectives: To establish normal values of cardiac chambers, valve annulus, great vessel, and thymus dimensions, to assess inter-observer variability, and to evaluate the effect of confounding factors on the measurements obtained. Research Methods: This descriptive, cross-sectional study evaluated cardiac chamber, valve annuli, thymus, and great vessel dimensions in Black South African neonates with normal hearts using echocardiography. Collected data was analyzed using excel, XLSTAT 2019 and STATISTICA version 13.5.0 statistical packages. A p-value of less than 0.05 was considered statistically significant. The inter-observer variability was tested using Pearson’s correlation coefficient to detect bias. Weight was used to correlate measurements to body size and mean values of each echocardiographic measurement was expressed as Z-scores. Results: Z-scores and the boundaries for all measurements are presented graphically. Body weight showed a positive correlation with all cardiovascular dimension measurements. Similarly, mode of delivery, gender and body surface area showed good correlation for most cardiac dimensions. Inter-observer variability revealed a strong correlation with most measurements. Conclusion: Nomograms from data acquired from healthy neonates are presented, which contributes to the current body of knowledge on cardiac dimensions in the African neonatal age group.